2020
DOI: 10.1002/ijfe.1775
|View full text |Cite
|
Sign up to set email alerts
|

Financial inclusion and human development in frontier countries

Abstract: This study empirically investigates whether the level of human development drives greater financial inclusion, and vice versa in the contexts of frontier markets. The dynamic panel generalized methods of moments (System‐GMM) methodology is employed to analyze data spanning from 2005 to 2014 for twenty (20) frontier markets by Standard and Poor's Indices. The study finds that human development is a catalyst for financial inclusion scale‐up in the banking industry, which in turn, augments the development process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 40 publications
(61 reference statements)
6
33
0
1
Order By: Relevance
“…The two-way causality between these two variables is also discussed [64]. Prior studies have found FI and human development to be positively correlated [65,66], including one study of frontier countries from 2005 to 2014, where low human development was associated with low financial inclusion [67]. Thus, our study also hypothesizes:…”
Section: Hypothesis 1a (H1a) Financial Inclusion Increases Economic Growth In South Asiamentioning
confidence: 63%
“…The two-way causality between these two variables is also discussed [64]. Prior studies have found FI and human development to be positively correlated [65,66], including one study of frontier countries from 2005 to 2014, where low human development was associated with low financial inclusion [67]. Thus, our study also hypothesizes:…”
Section: Hypothesis 1a (H1a) Financial Inclusion Increases Economic Growth In South Asiamentioning
confidence: 63%
“…However, financial inclusion has the tendency to reduce the size of shadow economy by bringing individuals out of the informal sector into the formal sector of the economy. It focuses on ensuring that a greater proportion of the population isactively engaged in the opportunities and processes available in the formal economic activities through mainstream financial system (Ababio et al , 2020). It is a situation where individuals and firms (small or medium) have access to useful and affordable financial products and services that meet their needs.…”
Section: Introductionmentioning
confidence: 99%
“…The system GMM approach has been used in many previous empirical health-related studies (32). Following Immurana et al (31,34), we use the dynamic panel-data model (2). This econometric specification is widely used in the empirical finance literature to examine the nexus between financial inclusion and human development.…”
Section: Model and Methodsmentioning
confidence: 99%